Endoscopic decompression in colonic distension - Belle, Sebastian (Visceral medicine, 2021)
Background: Acute colonic distension is a medical emergency with high morbidity and mortality. Clinically important causes of colonic distension are acute colonic pseudo-obstruction, colonic volvulus, and malignant obstruction. Endoscopic decompression is one established therapeutic strategy. Summary: This therapeutic review will give an overview of possible therapeutic strategies based on the recently published literature, focusing on endoscopic decompression and summarizing the other therapeutic possibilities. The review discusses separately the therapeutic options of acute colonic pseudo-obstruction, colonic volvulus, and malignant obstruction, providing an evidence-based orientation for clinical use. Key Messages: Endoscopic decompression of colonic distension is an established therapy with high clinical success. The technique and its position in the therapy sequence differ depending on the medical condition, the trigger of the colonic distension, and the local expertise.